From principles to protection: Leadership in uniting integrity and ethics for research security - Seán Lacey; Tom Farrelly; Tara Doherty; Suzanne McMurphy; Áine de Róiste (Societal Impacts, 2025)
In today's global research landscape, ensuring integrity and security is critical. The CORRIE - Collaborative Open Resources on Research Integrity and Ethics - project brought together an international, multidisciplinary, cross-jurisdictional team to develop practical principles and resources for research integrity and ethics. Using a values-driven, collaborative leadership model, the team co-created tools grounded in authenticity and accountability, establishing an actionable framework. These resources should effectively address research security, fostering a resilient, effective research culture. Through a user-informed methodology and inclusive collaboration, the project team translated principles into tangible tools reinforcing ethical conduct in daily practice. This approach ensures robust protections without stifling crucial innovation. The CORRIE project offers notable societal value, bolstering research credibility and trustworthiness. It advances equity by providing shared standards for all researchers, clearly demonstrating that integrity, ethics, and security are interconnected and mutually reinforcing. This significant work meaningfully contributes to United Nations Sustainable Development Goals (SDGs) 4, 9, 16, and 17, fostering quality education, robust innovation, strong institutions, and effective partnerships.